(untitled) (JOURNAL OF ANCIENT HISTORY AND ARCHAEOLOGY, 2025)
During the last decade, archaeological research carried out at Istros and other points of interest in the western Black Sea has led to the discovery of some rare or even unique pre-coinage monetary instruments. Presented in this regard, are a primary lead sample, a commercial coin showing the representation of a sturgeon fish, and a silver Olbian dolphin. These discoveries add new information regarding the origin of pre-coinage monetary instruments and their role in the Greek colonies and, subsequently, in the autochthonous environment of the western Black Sea. Also included are the results of interdisciplinary analyses (X-Ray Fluorescence and micro-PIXE – Proton Induced X-ray Emission) done on approximately 300 specimens from the category of those instruments that were cast for commercial purposes of the laurel leaf/olive leaf/wheat grain types.